Use of Polyaxial Locking Plate and Rod Reconstruction in the Treatment of Femur Fractures in Dogs: A Clinical Study - vallem, keerthi; Reddy K, Jagan Mohan; M., Sravanti; Kumar S, Ranjith (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Polyaxial Locking Plates (PAX) combines the advantages of conventional locking bone plates along with variable angle screw insertion, with a locking screw angulation range of up to 15o off the central axis. Clinical, orthopaedic examination and survey radiographs revealed the femur fractures in six cases. Polyaxial Locking Plate in conjunction with an Intramedullary pin (IMP) was used to stabilize the femoral fractures in dogs of different breeds and genders. Clinical and haemato-biochemical evaluation was carried out post-operatively at periodic intervals to ascertain the heath and fracture healing. Radiographic examination was conducted on days 0, 30th, 60th and 90th post-operatively. Haemato-biochemical findings did not vary between periods and were within normal range, except serum ALP which showed peak value at 15th post-operative day with gradual reduction thereafter. Minimal contact of PAX plate with the bone resulted in preservation of periosteal blood supply, which promoted early fracture healing, limb ambulation and an earlier return to normal range of motion. A complication of Pin migration was observed in two dogs.